Defeated Heroes: The Representation of Women in the Film Women from Rote Island - Namira Choirani Fajri; Nonny Rulisty Putri Sutikno (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study aims to analyze the representation of women in the film